Teacher competence in implementing higher-order thinking skills oriented learning in elementary schools - Wandika Wita Susilowati; Suyatno Suyatno (Universitas PGRI Madiun, 2021)
Information and technology development in the last decade have caused fundamental changes in all of the life aspects, including in the educational aspect. Learning in the school was demanded to be an agent of instilling the ability of higher-order thinking (HoTS) so that the students could deal with life challenging in future life. The teachers also must have competence in implementing HoTS oriented learning. This study aimed to explore teachers’ competencies and implement HoTS oriented learning in the public elementary school 2 of Ketaon, Boyolali Regency. Data was collected through interviews, observation, and documentation. The data collected further were analyzed by using the data analysis technique of the interactive inductive model of Miles and Huberman. The the research results showed that 1) there are five competencies used by the teachers in implementing HoTS oriented learning as follows; Educational Competence, Competence for Technological Commercialization, Competence in Globalization, Competence In Future Strategies, and Counsellor Competence. 2) Efforts made by teachers are to improve competence in implementing HoTS oriented learning by following the training and education program, participating in the empowerment of professional teacher development organizations such as teachers’ cluster working groups (KKG), teacher working group (MGMP), webinar, technical guidance, and workshop. In addition, the role of colleagues contributed to increasing teachers’ competencies